Hoyos, L.E. (Comp.). (2005). Relativismo y racionalidad. Bogotá: Unibiblos/Universidad Nacional de Colombia. ISBN: 958-701-494-4. Número de páginas: 425. - Monsalve, Luisa; Universidad Externado de Colombia (2006)
null